Assessing Gender Gaps in Employment and Earnings in Africa: The Case of Eswatini - Zuzana Brixiova; Susumu Imai; Thierry Kangoye; Nadege Desiree Yameogo (Institute of Labor Economics (IZA), 2021)
Persistent gender gaps characterize labor markets in many African countries. Utilizing Eswatini's first three labor market surveys (conducted in 2007, 2010, and 2013), this paper provides first systematic evidence on the country's gender gaps in employment and earnings. We find that women have notably lower employment rates and earnings than men, even though the global financial crisis had a less negative impact on women than it had on men. Both unadjusted and unexplained gender earnings gaps are higher in self-employment than in wage employment. Tertiary education and urban location account for a large part of the gender earnings gap and mitigate high female propensity to self-employment. Our findings suggest that policies supporting female higher education and rural-urban mobility could reduce persistent inequalities in Eswatini's labor market outcomes as well as in other middle-income countries in southern Africa.
Keywords: J16; J21; L26; O12; 330; gender; employment; income; multivariate analysis; policies